Mineralogical And Deportment Study Of Gold Using Diagnostic Leaching Experiment - Shaik Abdul Wahab, Shaik Abdul Rahman (2019)
The as-received gold ore samples from Kuala Lipis, Pahang was used in the deportment study of gold using diagnostic leaching experiment. Prior to the design of diagnostic leaching experiment, mineralogical characterization were conducted on the gold ore sample. Physical properties study on rock samples using visual observation showed the mineralization of quartz veins associated with sulphide minerals. OM study on the thin and polished sections samples showed that the gold was found interlocked with pyrite, arsenopyrite, quartz and galena. XRF, XRD and ICP-OES analysis were conducted on the ground gold ore samples. From XRF analysis, the major component present was SiO2 (81.14 %), followed by Al2O3 (11.18 %). Other significant compounds present were Fe2O3, K2O, SO3, As2O3, MgO and PbO. Mineral phases detected by XRD analysis were quartz, pyrite and arsenopyrite. These findings compliment XRF and OM study which led to the conclusion that the gold ore sample received contained gold in association with sulphide and silicate minerals. From fire assay technique and cyanide bottle roll test, the total gold and free milling gold were about 31.38 g/t and 16.79 g/t, respectively. ICP-OES analysis on the acid digested samples gave a significant amount of As, Fe and Pb. The diagnostic leaching experiment that follows gave about 18.48 % of gold found interlocked in arsenopyrite and pyrite, 14.18 % gold in base metal sulphides and labile pyrite, 10.07 % gold in sulphide concentrate and 3.41 % gold in galena, with the final residue carrying about 1.80 g/t of gold in silicate (quartz).